1966
DOI: 10.2135/cropsci1966.0011183x000600030013x
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Correlations, Dominance, and Heritability of Quantitative Characters in Oats1

Abstract: Three methods of estimating dominance were applied to F1 data on plant height, panicle number, heading date, number of spikelets per panicle, number of panicles per plant, and grain yield from the 15 diallel crosses among 6 oat varieties. Genotypic correlations and heritability percentages, in the broad sense, were calculated for the F2.In general, the dominance values from the 3 methods of estimation were in good agreement with one another and with the observed effects. Overdominance was indicated for number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
3

Year Published

1970
1970
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(8 citation statements)
references
References 9 publications
0
5
0
3
Order By: Relevance
“…Nas gramíneas em geral, especialmente em cereais, o ciclo possui alta herdabilidade, conforme detectado em trigo (EHDAINE & WAINES, 1989), aveia (PETR & FREY, 1966;MITTELMANN et al, 2001) e cevada (FREY, 1954). Também para o azevém as herdabilidades realizadas geralmente são altas (NELSON et al, 1997).…”
Section: Resultsunclassified
“…Nas gramíneas em geral, especialmente em cereais, o ciclo possui alta herdabilidade, conforme detectado em trigo (EHDAINE & WAINES, 1989), aveia (PETR & FREY, 1966;MITTELMANN et al, 2001) e cevada (FREY, 1954). Também para o azevém as herdabilidades realizadas geralmente são altas (NELSON et al, 1997).…”
Section: Resultsunclassified
“…In this current investigation, a high heritability was observed for pollen viability. Previous research has consistently shown that high heritability implies minimal environmental influence on the genotype [59][60][61]. Therefore, minimized environmental effect on the studied trait allowed the high accuracy of 94% in the selection of genotypes under the HS conditions [40,[62][63][64].…”
Section: Pollen Sizementioning
confidence: 99%
“…Menurut Syukur et al (2009) kriteria nilai heritabilitas adalah rendah = h 2 bs < 0.2; sedang = 0.2 < h 2 bs < 0.5; dan tinggi = h 2 bs > 0.5, untuk kriteria antara heritabilitas arti sempit dan heritabilitas arti luas adalah sama (Reddy & Jabeen, 2016). Pendugaan rasio dominansi dihitung berdasarkan rumus pendugaan potensi rasio (hp) yang disarankan oleh Laurentin & Karlovsky (2006); Petr & Frey (1966) yaitu hp= (F 1 -MP)/(HP-MP), dimana F 1 adalah rata-rata F 1 , HP adalah rata-rata tetua tahan, dan MP adalah nilai tengah kedua tetua. Berdasarkan nilai potensi rasio, derajat dominansi diklasifikasikan sebagai: hp = 0 (tidak ada dominansi); hp = 1 atau hp = -1 (dominan atau resesif penuh); 0 < hp < 1 (dominan parsial; -1 < hp < 0 (resesif parsial); dan hp > 1 atau hp < -1 (overdominansi).…”
Section: Pendahuluanunclassified